Assessment of seed quality along the rice seed value chain in Tanzania. Issue 7 (3rd October 2019) - Gebeyehu, Setegn; Kangile, Joseph; Mwakatobe, Emmanuel
ABSTRACT: This article reports on a study that assessed the qualities of rice seeds collected from formal and informal channels in Tanzania. Seed sources used by farmers and the seed selection and management practices followed also were examined. More than 90% of farmers' seed samples met the national standards for key seed quality parameters. Field grow-out tests revealed that only about a fifth of the samples from the two systems met the minimum standard for genetic purity. Because most farmers rely on their own saved seed, enhancing skills in seed selection and maintenance is needed to ensure higher paddy productivity and marketability.